Vibrio cholerae FeoB hydrolyzes ATP and GTP in vitro in the absence of stimulatory factors() - Gómez-Garzón, Camilo (Metallomics, 2020)
Feo is the most widely conserved system for ferrous iron transport in prokaryotes, and it is important for virulence in some pathogens. However, its mechanism of iron transport is not fully understood. In this study, we used full-length Vibrio cholerae FeoB (VcFeoB) as a model system to study whether its enzymatic activity is affected by regulatory factors commonly associated with FeoB proteins from other species or with G-proteins that have homology to FeoB. VcFeoB showed a higher rate of hydrolysis of both ATP and GTP than its N-terminal domain alone; likewise, ions such as K(+) and Fe(2+) did not modulate its nucleotide hydrolysis. We also showed that the three V. cholerae Feo proteins (FeoA, FeoB, and FeoC) work in a 1:1:1 molar ratio in vivo. Although both FeoA and FeoC are required for Feo-mediated iron transport, neither of these proteins affected the VcFeoB NTPase rate. These results are consistent with an active transport mechanism independent of stimulatory factors and highlight the importance of using full-length FeoB proteins as a reliable proxy to study Feo-mediated iron transport in vitro.